The construction of authorial voice in writing research articles: A corpus-based study from an APPRAISAL theory perspective - Zhang, Weiyu; Cheung, Yin Ling (International Journal of English Studies, 2018)
This study explores voice from an APPRAISAL theory perspective. It aims to investigate how published research writers deploy ATTITUDE and GRADUATION resources to review existing literature in the field. The study is based on a corpus of literature reviews (LRs) from 204 research articles (RAs) in computer networks and communications (CNC) and second language writing (SLW). Findings show that 1) writers demonstrate a strong preference to express their attitude through APPRECIATION rather than AFFECT and JUDGEMENT resources; 2) more FORCE than FOCUS resources are used to upgrade attitudinal meanings realized through ATTITUDE resources or to evoke APPRECIATION; and 3) one-way ANOVA and post hoc tests have detected significant differences in the use of AFFECT and JUDGEMENT resources and in two sub-categories of FORCE and FOCUS resources. The study contributes to new knowledge by relating ATTITUDE and GRADUATION resources to the construction of voice in the disciplines of CNC and SLW.